(untitled) (Bangladesh Journal of Microbiology, 2020)
The scientific literatures on clinical manifestations of coronavirus disease 2019 (COVID-19) patients from South Asian countries including Bangladesh are limited. Documentation of clinical spectrum from various geographic locations is vital for future scientific studies and clinical management. This study is aimed to report the sociodemographic and clinical characteristics of noncritical patients with COVID-19 in Bangladesh. We conducted a cross-sectional study at three dedicated COVID-19 hospitals of Bangladesh. The severity of the COVID-19 cases was assessed based on the WHO interim guidance. Data were collected only from non-critical COVID-19 patients as critical patients required immediate management. A total of 103 real-time polymerase chain reaction (RT-PCR) confirmed noncritical COVID- 19 patients were included. Most of the patients (71.8%) were male. Mild, moderate and severe illness were assessed in 74.76%, 9.71% and 15.53% of patients respectively. Nearly 52.4% patients had a co-morbidity, with hypertension being the most common (34%), followed by diabetes mellitus (21.4%) and ischemic heart disease (9.7%). Fever (78.6%), weakness (68%) and cough (44.7%) were the most common clinical manifestations. Other common symptoms included loss of appetite (37.9%), difficulty in breathing (37.9%), loss of taste or smell (35.0%), headache (32%) and body ache (32%). The median time from onset of the first symptom to attending hospitals was 7 days (interquartile range: 4 - 10). This study will help both the clinicians and epidemiologists to understand the magnitude and clinical spectrum of COVID-19 patients in South Asian perspective including Bangladesh. Bangladesh J Microbiol, Volume 37 Number 2 December 2020, pp 42-46